2018
DOI: 10.1021/acscatal.7b03723
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Preparation with Plasmas: How Does It Work?

Abstract: Catalyst preparation with plasmas is increasingly attracting interest. A plasma is a partially ionized gas, consisting of electrons, ions, molecules, radicals, photons, and excited species, which are all active species for catalyst preparation and treatment. Under the influence of plasma, nucleation and crystal growth in catalyst preparation can be very different from those in the conventional thermal approach. Some thermodynamically unfavorable reactions can easily take place with plasmas. Compounds such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
280
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(286 citation statements)
references
References 202 publications
4
280
0
2
Order By: Relevance
“…It was reported that cobalt nitrate was directly converted into Co 3 O 4 when it was calcined in air atmosphere, whereas in this work, based on XRD, XPS and TPR results, plasma assisted decomposition of cobalt nitrate either in the form of Co(NO 3 ) 2 ⋅ xH 2 O or mixture of Co 3 O 4 and Co(NO 3 ) 2 resulted in the formation of large amount of CoO, partial reduction was happened during the plasma treatment in air atmosphere. In non‐hydrogen glow discharge plasma field, electrons, hydrated electrons, and many other reduction active species could lead to the effective reduction of metal ions with positive standard electron potentials ,. It is documented that the standard electron potential of Co 3+ to Co 2+ is 1.83 eV and that of Co 2+ to Co 0 is −0.28 eV, thus in this work, the reduction of Co 3 O 4 to CoO may occur during the plasma treating process.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…It was reported that cobalt nitrate was directly converted into Co 3 O 4 when it was calcined in air atmosphere, whereas in this work, based on XRD, XPS and TPR results, plasma assisted decomposition of cobalt nitrate either in the form of Co(NO 3 ) 2 ⋅ xH 2 O or mixture of Co 3 O 4 and Co(NO 3 ) 2 resulted in the formation of large amount of CoO, partial reduction was happened during the plasma treatment in air atmosphere. In non‐hydrogen glow discharge plasma field, electrons, hydrated electrons, and many other reduction active species could lead to the effective reduction of metal ions with positive standard electron potentials ,. It is documented that the standard electron potential of Co 3+ to Co 2+ is 1.83 eV and that of Co 2+ to Co 0 is −0.28 eV, thus in this work, the reduction of Co 3 O 4 to CoO may occur during the plasma treating process.…”
Section: Resultsmentioning
confidence: 79%
“…During thermal calcination, a slow nucleation and a fast crystal growth are taken place, higher calcination temperature would lead to further sintering of metal particles and thus particle size increases . As to the plasma assisted precursor decomposition process, active species, especially the high energetic electrons are abundant in the plasma field, which could very fast react with catalyst precursor and lead to the rapid nucleation; meanwhile, due to the low operation temperature (low gaseous temperature), the crystal growth is quite slow ,. This could explain why the plasma treatment enhanced the dispersion of cobalt species in different degrees, in comparison with their calcined counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted here that the surface areas of the three Ni/La 2 O 3 catalysts are slightly higher than the corresponding supports, probably resulted from the formation of new LaNiO 3 phase, which is detected by XRD for all the three catalysts (Figure (B)). With GNC and PP method, La 2 O 3 supports possessing higher surface areas can be obtained, which could promote the dispersion of the active Ni species on the prepared Ni/La 2 O 3 catalysts, and might eventually promote the activity, stability and anti‐coking coke ability of the related catalysts in DRM …”
Section: Resultsmentioning
confidence: 99%
“…With GNC and PP method, La 2 O 3 supports possessing higher surface areas can be obtained, which could promote the dispersion of the active Ni species on the prepared Ni/La 2 O 3 catalysts, and might eventually promote the activity, stability and anti-coking coke ability of the related catalysts in DRM. [31] GNC method, La 2 O 3 -GNC supports possessing the smallest crystallite size and largest surface area can be obtained. Figure 2(B) exhibits the XRD patterns of the freshly calcined Ni/La 2 O 3 catalysts.…”
Section: N 2 Adsorption-desorption Measurements On the Catalystsmentioning
confidence: 99%
“…The S BET of PC-PT was increased by nearly 10 m 2 g −1 as compared to that of PC-T, which indicated that catalysts' morphologies were modified by the plasma. This might be ascribed to the fact that plasma-excited species etched the catalyst surface [19] and some of the CeO 2 nanorods were cracked and became shorter, exposing more of the catalysts' surface area. The decrease of S BET was attributed to sintering of the catalysts at high temperatures.…”
Section: Introductionmentioning
confidence: 99%